A case study: the AFL as a positive institution - Densten Iain (Sciendo, 2021)
The Australian Football League (AFL) is a leading professional sports organization within the multi-billion-dollar entertainment industry. This case study uses publicly available information to investigate the AFL in terms of its credentials as a positive institution using the good work model developed by Stansbury and Sonenshein (2012). The AFL has taken advantage of the economic rationalism and developed a corporate structure able to deliver a range of good work activities. For example, developmental programs that help players exceeding high community expectations. This study suggests that the good work model is beneficial for cognitive resources, normal functioning, regulatory focus, and impression formation. The AFL appears to answer Cameron et al. (2004) call to identify and enable flourishing and life-giving aspects of their organisation and, thus, represents a kind of positive institution. Finally, the study recognizes positive institutions as worthwhile but raises concerns about the uniqueness and lack of cultural research.